Pelatihan Artificial Intelligence (AI) untuk Pengembangan Branding UMKM Gita Laras di Desa Pancot, Karanganyar - Irwan Christanto Edy; Suryo Adinugroho; Kristian Faskahariyanto; Truli Nugroho; Alexander Mario Retto Djong; Kunto Adi Rumekso (CV. ALIM'SPUBLISHING, 2026)
Advances in digital technology and Artificial Intelligence (AI) have transformed how Micro, Small, and Medium-sized Enterprises (MSMEs) develop brand identity and communicate with consumers. However, many food and beverage MSMEs still face challenges in utilizing AI to create attractive branding and effective digital marketing content. This community service program aimed to enhance the branding capabilities of culinary MSMEs through AI-based training. The program involved members of the Gita Laras Association in Pancot Village, Tawangmangu, Karanganyar. Activities included a needs assessment, training sessions, demonstrations of AI applications, practical exercises in creating logos, slogans, social media content, and product descriptions, followed by evaluations through branding assignments. The results showed significant improvements in participants’ understanding of digital branding concepts and practical skills in using AI tools. Participants successfully developed simple visual identities, engaging promotional materials, and more consistent digital communication strategies. They also demonstrated greater confidence in applying AI for marketing and business promotion. Overall, the program confirms that AI-based branding training effectively strengthens the digital capabilities, competitiveness, innovation, and sustainability of culinary MSMEs in the evolving digital economy.